‘Internet+’ comprehensive nursing training course in the post-epidemic era—an exploration of the mixed teaching mode: a randomized trial - Wang, Qing-Ling; Liu, Lan-Lan; Liu, Cheng-Rui; Zhu, Qing-Shuang; Ren, Zhi-Ying; Gang, Ting-Ting; Zhou, Chun-Yan; Li, Qiu-Ping; Chen, Xi; Han, Bin-Ru (Frontiers in Medicine, 2023)
Objective To explore the effect of the application of the ‘Internet+’ nursing teaching mode on the comprehensive teaching ‘Fundamentals of Nursing’. Trial design Parallel design and convenient sampling were used to select vocational nursing students from the Nursing College of Capital Medical University. Methods Selected students were randomly divided into two groups. The control group consisted of 30 students in Grade 2020 higher vocational nursing education (traditional teaching mode). The observation group consisted of 30 students in Grade 2021 higher vocational nursing education (Internet+ mixed teaching mode). Training assessment results, automatic learning ability, professional identity, and satisfaction were compared between the two groups. Results Compared with the control group, the students in the observation group scored higher in the following operation practices: venous blood sampling, intradermal injection, cardiopulmonary resuscitation (CPR), sputum aspiration, and putting on and taking off robes (84.01 ± 0.87 vs. 92.14 ± 1.23; 91.41 ± 0.82 vs. 96.86 ± 0.27; 87.56 ± 0.31 vs. 93.91 ± 2.79; 88.11 ± 0.51 vs. 93.75 ± 0.29; and 82.29 ± 0.29 vs. 90.96 ± 0.34, respectively, with p < 0.05 for all scores). The total scores for autonomous learning ability and subjective satisfaction were also higher in the observation group compared with the control group (82.98 ± 4.72 vs. 93.17 ± 5.01 and 96.67% vs. 90.00%, respectively, with p < 0.05 for all scores). Conclusion In the post-epidemic era, the ‘Internet+ hybrid teaching mode’ was applied to comprehensive nursing teaching. This changed the traditional education mode, which focuses only on professional knowledge. The ‘Internet+’ teaching mode results showed that the professional, ideological, and political courses exhibited the same value guidance, which improved students’ independent learning ability, practical operation ability, professional identity, and satisfaction.